Inteligencja i rewolucja w Łodzi w latach 1905–1907 - Iwańska, Marzena (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
The 1905–1907 Revolution in the Kingdom of Poland was a significant experience not only for workers, but also for other social classes, including the Intelligentsia. The Revolution was the moment when the Intelligentsia in Łódź emerged with such an intensity for the first time. It became active in the city’s social, political and cultural life. Owing to 1905–1907 events, the Intelligentsia became integrated as a social class and its identity became more defined. Mass protests of workers were perceived by majority of the Intelligentsia as unsettling. They was seen a threat to the social peace and order and the city’s economy since they often turned into violent fratricidal fights, which were detrimental to the city’s material and moral condition. The Intelligentsia saw its main role in improving workers’ education, which might draw them away from the revolutionary movement. Many ideas and initiatives of the Intelligentsia concerning workers seem to have been belated or inadequate in the view of the torrid revolutionary period. Politically, a major part of Łódź Intelligentsia was connected with the liberal and national movement. For them, the highest value of 1905–1907 events was the opportunity to gather and organise educational associations, lectures and Polish language classes. The period is usually referred to as “years of freedom” and perceived as the time when the Polish society, including its Intelligentsia, unprecedentedly revived for the first time in years.